Mental health service contact following release from prison or hospital discharge in those with psychosis - Chowdhury, Nabila Z.; Wand, Handan; Albalawi, Olayan; Adily, Armita; Kariminia, Azar; Allnutt, Stephen; Sara, Grant; Dean, Kimberlie; Ellis, Andrew; Greenberg, David; Schofield, Peter W.; Butler, Tony (Frontiers in Psychiatry, 2022)
Background An association exists between psychosis and criminal offending, which evidence suggests can be reduced by effective mental health care for this vulnerable population. However mental health services often lose contact with people after diagnosis. The association between the first episode of psychosis and criminal offending highlights the need for effective mental health care for this vulnerable population. Aims To investigate the association between the first diagnosis of psychosis (FDP) in prison or hospital and subsequent mental health service contact following release from prison or discharge from hospital. Materials and methods Individuals with a FDP either in prison (n = 492) or hospital setting (n = 24,910) between July 2006 and December 2011 in NSW (Australia), were followed post-release or discharge until their first mental health service contact in the community, the occurrence of an offence, death, or completion of the study period at the end of December 2012. Cox regression models were used to examine the predictors for the mental health service contacts following release or discharge. Results Over 70% of those with a FDP in prison or hospital had a psychosis-related or any community-based mental health service contact following release or discharge between July 2006 and December 2012. Those with a FDP in prison were more likely to have no contact with mental health services than those in hospital with no prior offence record (hazard ratio, HR = 3.14, 95% CI: 2.66–3.72 and adjusted hazard ratio, aHR = 3.05, 95% CI: 2.56–3.63) within a median follow-up time of 25 days for the prison group and 26 days for hospital group. Males, individuals of Aboriginal heritage and individuals diagnosed with substance-related psychoses compared to those with schizophrenia and related psychoses were less likely to have a mental health service contact following release or discharge in both the univariable and multivariable analysis. Conclusion This study suggests that prior offending or a previous prison episode represents a barrier to mental health service contact in the community for those with a FDP. Effective rehabilitation planning while exiting prison and discharge planning from hospital are essential to the successful reintegration of these individuals with a FDP.